Stress and Coping Styles of Parents with Children with Learning Disabilities - Azzahrah, Anuar; Edris, Aden; Fatahyah, Yahya; Nor Mazlina, Ghazali (Universal Publishers, 2021)
Having children with learning disabilities brings life-changing implications in the lives of the whole family. This purpose of the study was to investigate the levels of stress based on the characteristics of parents of children with learning disabilities and coping strategies among these parents. 274 parents of children with learning disabilities have been selected as respondents of the study. A quantitative, cross-sectional survey design has been utilized in the study and was conducted at the community-based rehabilitation (CBR) centers in Malaysia. Based on the findings, there were high levels of stress experienced by parents of children with learning disabilities. There were no significant stress level differences between father and mother in the study. Parents of children with higher educational background and socioeconomic status tend to feel more stressful than those with lower educational background and socioeconomic status. The emotion-based coping strategies were reported to be the most frequently used by the parents. The study has also found significant differences in the parental stress level based on race, educational level, and occupation. The findings were essential in planning intervention programs or activities for parents with learning disabilities who registered their children under the CBR center.